Consciousness and Attention: On Sufficiency and Necessity - Van Boxtel, Jeroen J.; Tsuchiya, Naotsugu; Koch, Christof (Frontiers in Psychology, 2010)
Recent research has slowly corroded a belief that selective attention and consciousness are so tightly entangled that they cannot be individually examined. In this review, we summarize psychophysical and neurophysiological evidence for a dissociation between top-down attention and consciousness. The evidence includes recent findings that show subjects can attend to perceptually invisible objects. More contentious is the finding that subjects can become conscious of an isolated object, or the gist of the scene in the near absence of top-down attention; we critically re-examine the possibility of ‘complete’ absence of top-down attention. We also cover the recent flurry of studies that utilized independent manipulation of attention and consciousness. These studies have shown paradoxical effects of attention, including examples where top-down attention and consciousness have opposing effects, leading us to strengthen and revise our previous views. Neuroimaging studies with EEG, MEG and fMRI are uncovering the distinct neuronal correlates of selective attention and consciousness in dissociative paradigms. These findings point to a functional dissociation: attention as analyzer and consciousness as synthesizer. Separating the effects of selective visual attention from those of visual consciousness is of paramount importance to untangle the neural substrates of consciousness from those for attention.